Integrasi Maqāṣid Syarī‘ah dalam Penataan Peran Ganda Perempuan Perspektif Al-Qur’an - Aisyah Putri Salsabila; Nasrulloh (Al-Kindi, 2026)
Increased participation of women in the workplace raises challenges regarding the arrangement of dual roles in order to remain in harmony with Islamic values. This study aims to analyze how the principles of Maqāṣid Syarī‘ah can be integrated into the management of women's domestic and public roles based on the perspective of the Qur'an. The method used is a literature study with thematic analysis of Qur'anic verses, classical and contemporary maqāṣid literature, and modern Islamic gender studies. The results show that the five main principles of Maqāṣid Syarī‘ah, namely ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-‘aql, ḥifẓ al-nasl, and ḥifẓ al-māl provide an ethical framework that helps balance family responsibilities and professional roles. The integration of maqāṣid values enables the optimization of intellectual potential, protection of oneself and one's family, and increased economic contribution without neglecting household harmony. This study confirms that women's involvement in the workforce does not conflict with Islamic values as long as there is structural support and awareness of the principle of balance. These findings contribute to the development of a maqāṣid-based conceptual model relevant to the needs of working women in the modern era.